Human Factors and Organizational Issues Section Synopsis IMIA Yearbook 2021 - Senathirajah, Yalini; Hribar, Michelle; Section Editors of the IMIA Yearbook Section on Human Factors and Organizational Issues (Yearbook of Medical Informatics, 2021)
Objective: To select the best papers that made original and high impact contributions in the area of human factors and organizational issues in biomedical informatics in 2020.Methods: A rigorous extraction process based on queries from Web of Science® and PubMed/Medline was conducted to identify the scientific contributions published in 2020 that address human factors and organizational issues in biomedical informatics. The screening of papers on titles and abstracts independently by the two section editors led to a total of 1,562 papers. These papers were discussed for a selection of 12 finalist papers, which were then reviewed by the two section editors, two chief editors, and by three external reviewers from internationally renowned research teams.Results: The query process resulted in 12 papers that reveal interesting and rigorous methods and important studies in human factors that move the field forward, particularly in clinical informatics and emerging technologies such as brain-computer interfaces. This year three papers were clearly outstanding and help advance in the field. They provide examples of applying existing frameworks together in novel and highly illuminating ways, showing the value of theory development in human factors. Emerging themes included several which discussed physician burnout, mobile health, and health equity. Those concerning the Corona Virus Disease 2019 (Covid-19) were included as part of that section.Conclusion: The selected papers make important contributions to human factors and organizational issues, expanding and deepening our knowledge of how to apply theory and applications of new technologies in health.
Keywords: Human factors; human-computer interaction; organizational issues; electronic health records; mobile health